Agroecological strategies for Sitophilus zeamais handling in maize stored - Matías, Areli; Pérez, Betzabeth; Aragón, Agustín; Juárez, Dionicio; López, Jesús; Aragón, Miguel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Sitophilus zeamais is an economically important pest because it feeds on stored corn, since its control is carried out with increasingly toxic insecticides, the objective of the effect of more ecological alternatives such as the application of CaO (quicklime 2 %), Beauveria bassiana (1.109 espores.mL-1), Ricinus communis powder aqueous (1,5 %), modified atmosphere storage (20 L silo) and airtight environment (in barrel of 20 L) on the incidence and damage of S. zeamais in stored corn, in the municipality of Tlacotepec de Benito Juarez, Puebla. The experiment was carried out under a completely randomized block design with five repetitions, where the five control methods mentioned above were tested and compared with a control treatment (plastic bag). Quicklime, storage in a modified atmosphere and storage in a hermetic environment significantly decreased (Tukey, p <0.05) the number of weevils in corn grains during 247 days of storage and the percentage of damage to the grains remained below from 1 %. Therefore, these results showed that the application of quicklime, airtight environment and storage in a modified atmosphere controlled the damage caused by S. zeamais and are highly favorable for the conservation and protection of stored corn grains.